Gender Differences in the Physical and Psychological Manifestation of Childhood Trauma and/or Adversity in People with Psychosis - Sweeney, Shaun; Air, Tracy; Zannettino, Lana; Shah, Sonal S.; Galletly, Cherrie (Frontiers in Psychology, 2015)
The link between childhood trauma and/or adversity and risk of psychosis is well known. Our aim was to determine the prevalence of childhood trauma and/or adversity in people who have psychotic disorders and to investigate the association between childhood trauma and/or adversity and a range of social and health measures. Participants (n=391, 42% male) were specifically asked about any experience of childhood trauma and/or adversity. Respondents provided information about education, employment, physical health and health service utilisation. Univariate analyses revealed that childhood trauma and/or adversity was associated with poorer levels of self-reported physical health and social problems. This includes the experience of chronic pain, headaches, arthritis, asthma and victimisation/stigma in men. Participants with a childhood trauma and/or adversity history indicated higher rates of lifetime suicide attempts with women reporting more lifetime depressive symptoms. Multivariate analyses revealed differing profiles in relation to physical and psychological health variable between males and females. Males with the experience of childhood trauma and/or adversity were significantly more likely to report cardiovascular/stroke issues, migraines and anhedonia. Females with the experience of childhood trauma and/or adversity were more likely to report a lifetime history of elevated mood and to be married or in a defacto relationship. There has been very little research into the assessment and treatment of the effects of childhood trauma and/or adversity in adults with psychosis. Childhood trauma and/or adversity may contribute to higher rates of self-reported poor health in men and is associated with increased depression in women. Our findings suggest that interventions to address the effects of past trauma are urgently needed.